al-Akhlaq bayna al-madrasatayn al-salafiyah wa al-falsafiyah : Miskawayh wa Ibn al-Qayyim namudhaj - 'Amru, 'Abd Allah ibn Muhammad ([al-Riyad] : al-Mamlakah al-'Arabiyah al-Sa'udiyah, Wizarah al-Ta'lim al-'Ali, Jami'ah al-Imam Muhammad ibn Sa'ud al-Islamiyah, Imadah al-Bahath al-Ilmi, 2006)
Islamic ethics; salafi school and philosophical; Islamic empire; virtues
Includes bibliographical references (p. 291-307)
Keywords: Ibn Miskawayh, Ahmad ibn Muhammad, -- d. 1030; Ibn Qayyim al-Jawziyah, Muhammad ibn Abi Bakr, -- 1292-1350; Ethics -- Islamic Empire; Values (Islam); Virtues; Islamic ethics